2015
DOI: 10.3126/jist.v20i2.13943
|View full text |Cite
|
Sign up to set email alerts
|

Pinworm (Enterobius vermicularis) Infection in Children of Barbhanjyang VDC, Tanahun District, Nepal

Abstract: The present study was carried out to determine the prevalence of Enterobius vermicularis in children of Barbhanjyang Village Development Committee, Tanahun, District, Nepal. A total of 110 Scotch tape (Cellophane tape) samples of children aged between 1-12 years were collected and microscopically examined. Altogether 14(12.72%) enterobias prevalence cases were reported in children including sixteen percent male and nine percent female cases. High prevalence of pinworm infection was the age group of 5-8 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Out of 107 school children, 10.28% enterobiasis was observed. This infection rate is similar to the 12.72% infection in previous finding of Nepal [17]. Similarly, the present finding is also consistent to other previous studies in Korea [18,19] and China [20].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Out of 107 school children, 10.28% enterobiasis was observed. This infection rate is similar to the 12.72% infection in previous finding of Nepal [17]. Similarly, the present finding is also consistent to other previous studies in Korea [18,19] and China [20].…”
Section: Discussionsupporting
confidence: 94%
“…The minimum prevalence of enterobiasis among 2-4 yrs age group might be due to the parental care specially by mothers. Similar result have also been reported in Iraq [31], in South Jordan [32], in Philippines [30], in Thailand [33], in Nepal [17].…”
Section: Discussionsupporting
confidence: 90%
“…Other studies showed that the prevalence of pinworm infections in children who have a habit of scratching their buttocks area is higher than in those that do not. Pinworm eggs in the perianal area can move to the hands when a child scratches their buttocks area, thereby increasing the risk of pinworm infections (Dahal & Maharjan, 2015;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%